Early Detection of Methicillin Resistance by Real-Time PCR in Staphylococci Isolated from Blood Cultures - MERİÇ KOÇ, MELİHA; Willke, Ayse; SAYAN, MURAT; Meric, MELİHA; MUTLU, BİRSEN (My University, 2012)
Bacteremia caused by methicillin-resistant Staphylococcus aureus (MRSA) has a significant morbidity and mortality. The aim of this study was to evaluate the efficiency of real-time polymerase chain reaction (Rt-PCR) targeting nuc and mec genes in the culture extracts of blood culture systems for the early diagnosis of MRSA. A total of 48 samples that gave positive growth signal in BACTEC 9000 MB (BD, USA) and stained as gram-positive cocci, were included in the study. The samples were collected between 2009 and 2010. VITEC 2 (bioMerieux, France) system was used for the identification and antibiotic susceptibility testing of the isolates. According to the culture results, 15 of the isolates were methicillin-resistant coagulase-negative staphylococci (MRCNS), four were MRSA, 14 were methicillin-susceptible coagulase-negative staphylococci (MSCNS) and 15 were methicillin-susceptible S.aureus (MSSA). However, Rt-PCR yielded 17 MRCNS, eight MRSA, 10 MSCNS and 13 MSSA results. Our findings indicated lack of concordance between blood culture and PCR technique. When the blood culture results were accepted as the gold standard for the determination of methicillin resistance, sensitivity, specificity, positive and negative predictive values of Rt-PCR were found as 73%, 62%, 56% and 78%, respectively. In conclusion, in contrast to the expectations, Rt-PCR was not considered as an appropriate method for the detection of MRSA in routine diagnosis.